Phytochemical and chemotaxonomic studies on Paraboea rufescens (Gesneriaceae). (June 2022) - Fu, Xianjie; Chen, Junlei; Xie, Ruixuan; Zhou, Liqiang; Wei, Yinghuan; Yuan, Chunmao; Huang, Liejun; Hu, Zhanxing; Hao, Xiaojiang; Gu, Wei
Abstract: A phytochemical investigation on the whole plant of Paraboea rufescens led to the isolation of 17 compounds including nine phenylethanoid glycosides (1 –9 ), two steroids (10 –11 ), two triterpenoids (12 –13 ), two dihydroflavones (14 –15 ), and two organic acids (16 –17 ). Their structures were elucidated by their spectroscopic data analysis. This is the first report of compounds from P. rufescens. The chemotaxonomic significance of P. rufescens and the other species among Gesneriaceae was also discussed. Phenylethanoid glycosides can be recognized as typical biomarkers for the genus Paraboea . Highlights: 17 compounds were first isolated from the whole plant of Paraboea rufescens . Compounds 1, 3, 9, 10, 12, and 14–16 were first isolated from the genus Paraboea. Phenylethanoid glycosides can be recognized as typical biomarkers for the genus Paraboea. Compounds 13 can serve as biomarkers for the family Gesneriaceae.